EFEKTIVITAS PENGGUNAAN BAHAN AJAR KETERAMPILAN MENULIS TEKS PROSEDUR BERBASIS E-FLIPBOOK PADA SISWA KELAS VII SMP NEGERI 1 PARUNGKUDA KABUPATEN SUKABUMI - Ridoillahy, Girin; Sarimanah, Eri; Nurjaman, Aam; Mukhtar, Ruyatul Hilal (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, UNPAK, 2024)
The Effectiveness of Using E-Flipbook Based Teaching Materials for Writing Procedure Texts for Class VII Students of SMP Negeri 1 Parungkuda, Sukabumi Regency. Abstract. The purpose of this study was to determine the procedural text writing skills of class VII students of SMP Negeri 1 Parungkuda, Sukabumi Regency and the obstacles experienced by class VII students of SMP Negeri 1 Parungkuda, Sukabumi Regency in improving procedural text writing skills by using e-flipbook based procedural text writing skills teaching materials. . The method used in this study is the experimental method, the data collection techniques used are tests, questionnaires, and observations. The population in this study were seventh grade students of SMP Negeri 1 Parungkuda, Sukabumi Regency. The sample of this research is class VII D as the experimental class and class VII F as the control class by using cluster random sampling technique. The first hypothesis is the effectiveness of using e-flipbook based procedural text writing skills in improving the ability to write procedural texts in seventh grade students of SMP Negeri 1 Parungkuda, Sukabumi Regency. this is evidenced by the obtaining of experimental class pretest data with an average value of 42.2 (low ability) in writing procedure text, while the experimental class posttest results in writing procedure text increased with an average value of 82.9 (able). The results of the calculation of the comparison of the mean of the experimental class and the control class using the t test formula, obtained the price data and db = 58. and obtained the price of and the price of . Thus, the value of t_count is greater than t_table or the price of because the value of< is 1,672,39. These results indicate that the use of procedural text writing skills based on e-flipbooks effectively improve procedural text writing skills in seventh grade students of SMP Negeri 1 Parungkuda, Sukabumi Regency. Keywords: Writing skills, procedural text, e-flipbook based teaching materials.